Application of the affine theorem to an orthotropic rectangular reinforced concrete slab continuous over two adjacent sides and simply supported on other two sides having a short side opening - Ravindra, M.; Rambabu, K.; Goli, H.B. (Journal of Structural Engineering, 2024)
An attempt has been made to apply the affinity theorem to determine collapse load of two-way orthotropic slab with a short side opening with two adjacent sides continuous and other two sides simply supported. Keeping in view the basic principles of yield line theory, all possible admissible yield line patterns for two adjacent sides continuous (TAC) are considered for the given configuration of the slab subjected to uniformly distributed load (udl). A computer program has been developed to solve the virtual work equations derived in this paper. Illustration of above methodology has been brought out with numerical examples. Relevant tables and charts for given data and the governing admissible failure patterns of the slab for different sizes of openings are presented using the affine theorem. In this paper, authors also present the transformation of orthotropic slab into an equivalent isotropic slab using the affine theorem. The analysis is carried out with aspect ratio of opening quite different to that the slab.